Performance analysis of real-time precise point positioning with GPS and BDS state space representation - Liu, Peng (2023)
The third-generation BeiDou Navigation Satellite System (BDS-3) has global networking in July 2020, multi-constellation Precise Point Positioning (PPP) with GPS, BDS-2 and BDS-3 has become a more accurate global positioning technique. With the improvement of state-space representation (SSR) in 22 Mar. 2021, an initial assessment of real-time PPP with 3 constellations is presented. Specifically, a unified form of observation equations with 3 constellations is proposed. While the qualities of GPS/BDS-2/BDS-3 real-time services at the mountpoint SSRA00CNE0 are better than ultra-rapid ephemeris and worse than rapid ephemeris. Finally, the 3-hour real-time PPP experiments based on 52 Multi-GNSS Experiment (MGEX) reference stations over 21 days are realized in static and simulated kinematic mode. There are the similar positioning accuracy and precision for GPS-only, GPS/BDS-2 and GPS/BDS-2/BDS-3. However, the convergence time of the GPS/BDS-2/BDS-3 reduces by 3.37% and 3.32% in static mode. And it reduces by 9.04% and 1.87% in simulated kinematic mode.